Manajemen Informasi Dalam Organisasi - Nasution, Julaika; Vientiany, Dini (Journal of Law, Education and Business, 2024)
Information management is critical for businesses to solve problems and seize opportunities in a rapidly evolving digital environment. Advances in information and communications technology have changed the way businesses run, interact with clients, and allocate their resources. The importance of information technology in improving operational effectiveness, facilitating better decision making, and increasing competitiveness is discussed in this article. However, with these benefits also come challenges such as data security, information integrity, and adapting to rapid regulatory changes. This research uses a literature review method to explore the basic concepts of information management in organizations, with a focus on the integration of information systems and information technology as a strategy to face these challenges. The results show that organizations need to deeply understand the technologies they use and develop appropriate strategies to maximize their benefits while reducing risks. Thus, this article provides important insights for organizational leaders in managing digital transformation and increasing competitiveness in a competitive global marketplace.